Empowerment of Robusta Coffee Farmers to Develop Entrepreneurs in Aceh Barat Based on Technology Application - Aulia, Muhammad Reza; Darmansyah, Dedy; Nugroho, Yoga; Safrika, Safrika; Nasution, Anisah; Tanjung, Yulia Windi (Universitas Ahmad Dahlan, 2023)
Background: The problems of robusta coffee farmer in Aceh Barat Regency are lack of insight into the downstream potential of robusta coffee, lack of business development ideas and farmer do not understand making financial reports, legality and business organizational systems. For this reason, assistance are needed to coffee farmers so that they develop their business and increase their income. Contribution: Increasing insight into potential utilization and marketing, entrepreneurial development ideas, business finance. Method: Community service was held on 11-13 November 2022 at Teuku Umar University. The approach taken is in the form of a process of education, training and mentoring focuses on three stages: (1) Education of potential beneficiaries and development of the Robusta coffee business (2) Assistance in preparing financial reports, business organization systems and technology adoption and (3) Socialization of efficient coffee marketing channels. Results: The process that goes through each stage is the purchase of red cherries for robusta coffee. There are 3 sub-districts that currently can become suppliers of robusta coffee in Aceh Barat Regency, namely Woyla Induk District, Samatiga District and Meureubo District. The three districts have taken samples and carried out the drying process to become green beans. After purchasing the fruit, the next stage is the process of drying, roasting, grinding and packaging. Conclusion: The participants who were accompanied were able to apply coffee powder packaging technology at IBT, understand the legality of the robusta coffee business, understand the marketing of the robusta coffee business